Cyclodextrin mediated efficient energy transfer between 4-amido-1, 8-naphthalimide and porphyrin. (September 2020) - Yu, Jie; Xiao, Sisi; Chen, Fenglin; Li, Liu; Xu, Guangyu
Abstract: A novel supramolecular conjugate was conveniently fabricated by the non-covalent interaction between 4-amido-1, 8-naphthalimide bridged permethyl-β-cyclodextrins and tetrasodium tetraphenylporphyrintetrasulfonate, which was comprehensively characterized by the methods of UV–Vis, NMR, AFM, and TEM, respectively. Significantly, the efficient excited energy transfer process from 4-amido-1, 8-naphthalimide to porphyrin was investigated, showing that efficiency of excited energy transfer is high to 99% within the artificial nanoassembly. Graphical abstract: Image 1